RELEVANSI MITOS KALI PEMALI DENGAN ETIKA LINGKUNGAN ISLAM - Leni Andariati (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
Mankind and environment has very intimate relationship in the perspective of Humans and the environment have a very close relationship in Islamic perspective. Both are creatures created by Allah in this universe. Such view becomes a local knowledge for people wrapped in the form of myths. One of the myths in Brebes is the Pemali river myth that was seen as having relevance to this view. This article reveals the meaning of the Pemali river myth and its relevance to Islamic environmental ethics. The study used a qualitative approach in which data were obtained from the field through semi-structured interviews that focus on the questions have been prepared before. This study found that the existence of Pemali river myth makes people believe in the existence of supernatural powers in the Pemali river environment, so that it has a good effect on their attitude in treating it. Thus, the community actually carry out the responsibility as the caliph of Allah, because Allah did not create nature only for the benefit of humans, but also all the species in it. This has a positive impact on people’s behavior towards the environment.